WIPO Treaty On GRATK: Implikasi dan Tantangan Bagi Indonesia Dalam Mencegah Biopiracy - Sari, Devina Puspita; Kinanti, Fatma Muthia (Universitas Islam Indonesia, 2026)
This study examines the implications of the WIPO Treaty on Intellectual Property, Genetic Resources and Associated Traditional Knowledge (GRATK Treaty) and analyzes the challenges of implementing its provisions within the Indonesian legal system to prevent biopiracy. The research focuses on the compatibility between the Treaty's international norms and Indonesia's domestic legal framework, particularly in relation to the patent regime, communal intellectual property, and access and benefit-sharing (ABS) mechanisms. This study employs a normative juridical method using statutory and conceptual approaches. The legal materials analyzed include the WIPO GRATK Treaty, Indonesia's Patent Law, Government Regulations on Communal Intellectual Property, sectoral regulations governing genetic resources, and relevant international instruments concerning the protection of traditional knowledge. The data were analyzed qualitatively through a systematic interpretation of legal norms to assess the harmonization and implementation of national regulations. The findings indicate that Indonesia has incorporated several provisions of the WIPO GRATK Treaty through the obligation to disclose the origin of genetic resources and/or associated traditional knowledge in patent applications, as well as through benefit-sharing provisions introduced under the amended Patent Law. Nevertheless, the implementation of these provisions continues to face significant challenges, including regulatory fragmentation across sectors, the lack of integration between genetic resource databases and the patent examination system, limited verification and enforcement mechanisms for disclosure obligations, and inadequate institutional coordination in implementing prior informed consent (PIC) and access and benefit-sharing (ABS) arrangements. This study concludes that the effective implementation of the WIPO GRATK Treaty in Indonesia depends on cross-sectoral regulatory harmonization, the strengthening of a patent examination system supported by integrated genetic resource databases, and enhanced institutional capacity for monitoring and enforcement. Such integration is essential for establishing an effective, coordinated, and sustainable legal framework for preventing biopiracy.